Analysis of Mechanical Properties of Bioplastics Based on Banana Peel Starch with Variations of Rice Straw Cellulose - Ety Jumiati; Miftahul Husnah; Sri Ayu Lestari (Lambung Mangkurat University Press, 2023)
Plastic waste is a serious problem for society because it harms the environment. The manufacture of bioplastics as a substitute for conventional plastics is still being developed to produce healthy and safe plastic packaging. This study aims to see how the mechanical characteristics obtained from the manufacture of plastic from natural materials by utilizing waste plantain peels and rice straws which are commonly found in Indonesia. Variations in composition in the manufacture of bioplastics using a mass ratio of rice straw cellulose and plantain peel starch include sample A (0:2); sample B (0.25:1.75); sample C (0.5:1.5); sample D (0.75:1.25) and sample E (1:1) (w/w). The process of making bioplastics is carried out by heating all materials using a hot plate at 70℃ for 1 hour. The characterization carried out in this study was a test of tensile strength, percent elongation, and modulus of elasticity. The test results show that the bioplastic with the best composition variation is found in sample E with a tensile strength value of 114.51 kgf/cm2, an elongation test value of 3.99%, and a modulus of elasticity of 2873.97 kgf/cm2. The tensile strength test value in this study was by ASTM D882-12, which is 104.72 kgf/cm2, and the value of the modulus elasticity is close to the ASTM D882-12, which is 3163.81 kgf/cm2.KEYWORDS : bioplastic; banana peel starch; rice straw cellulose, mechanical characteristic.